Sea surface and subsurface circulation dynamics off equatorial Peru during the last ~17 kyr. (27th July 2015) - Nürnberg, Dirk; Böschen, Tebke; Doering, Kristin; Mollier‐Vogel, Elfi; Raddatz, Jacek; Schneider, Ralph
Abstract The complex deglacial to Holocene oceanographic development in the Gulf of Guayaquil (Eastern Equatorial Pacific) is reconstructed for sea surface and subsurface ocean levels from (isotope) geochemical proxies based on marine sediment cores. At sea surface, southern sourced Cold Coastal Water and tropical Equatorial Surface Water/Tropical Surface Water are intimately related. In particular since ~10 ka, independent sea surface temperature proxies capturing different seasons emphasize the growing seasonal contrast in the Gulf of Guayaquil, which is in contrast to ocean areas further offshore. Cold Coastal Water became rapidly present in the Gulf of Guayaquil during the austral winter season in line with the strengthening of the Southeast Trades, while coastal upwelling off Peru gradually intensified and expanded northward in response to a seasonally changing atmospheric circulation pattern affecting the core locations intensively since 4 ka BP. Equatorial Surface Water, instead, was displaced and Tropical Surface Water moved northward together with the Equatorial Front. At subsurface, the presence of Equatorial Under Current‐sourced Equatorial Subsurface Water was continuously growing, prominently since ~10–8 ka B.P. During Heinrich Stadial 1 and large parts of the Bølling/Allerød, and similarly during short Holocene time intervals at ~5.1–4 ka B.P. and ~1.5–0.5 ka B.P., the admixture of Equatorial Subsurface Water was reduced in response to both short‐term weakening of Equatorial Under Current strength from the northwest and emplacement by tropical Equatorial Surface Water, considerably warming the uppermost ocean layers.